Low-Level Knowledge and Associated Factor of Sexual and Reproductive Health Rights Among Aksum University Students, Aksum Ethiopia - Berhe, Elsa Tesfa; Ayene, Mlite; Gebregyorgis, Tsigehana; Hagos, Merhawit Gebremeskel; Gebremeskel, Teferi Gebru (Frontiers in Public Health, 2022)
Background: Reproductive health rights in Africa are unknown. According to international studies, violations of reproductive health rights of young people, especially university students, and most of these violations are not reported due to lack of information and awareness of these rights. This study aimed to assess the level of knowledge and associated factors on sexual and reproductive health rights in Ethiopia. Methods: Institution-based cross-sectional study using an interviewer-administered and structured questionnaire was conducted. The study population was a student of the selected department between November 2018 to June 2019. A simple random sampling method technique was used to select 420 students. Bi-variate and multi-variate logistic regression analysis was performed. Results: The knowledge level of the respondents was 16.4%. The majority of students 205(51%) were in the age group less than 20 years. Male [AOR: 1.46, 95% CI: 1.09, 1.95]; coming from urban areas [AOR: 2.11, 95% CI: (1.02, 4.37)]; provision of sexuality education or lecture in departments [AOR: 1.39, 95% CI: 1.02, 1.91] and discussion about reproductive health with anyone else [AOR: 2.31, 95% CI: 1.48, 3.62] were significant association for the knowledge of sexual and reproductive health rights. Conclusions: Respondents' knowledge level was found very low. Therefore, strengthening students' lectures or education on reproductive health in the curricula of high school, encouraging discussions with parents and anyone might improve the knowledge towards sexual and reproductive health rights.